2020
DOI: 10.4103/ipj.ipj_212_20
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cyberchondria and its associations in dental students amid COVID-19 infodemic

Abstract: Background: Adverse psychological effect of pandemic includes not only increased levels of stress, anxiety, and depression but also cyberchondria - the problematic online health research behavior. It is thought that the distress and uncertainty of pandemic clubbed with information overload and its ambiguity have paved the way for cyberchondria. Students being the vulnerable population, the present study was an effort at understanding cyberchondria in students. Aim: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
15
0
4
Order By: Relevance
“…A total of 96 duplicate articles were deleted and 166 were excluded after a first screening of the titles and abstracts. After reading the remaining 43 articles in full, we finally included 13 in our meta-analysis [47][48][49][50][51][52][53][54][55][56][57][58][59]. Exclusion reasons are detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 96 duplicate articles were deleted and 166 were excluded after a first screening of the titles and abstracts. After reading the remaining 43 articles in full, we finally included 13 in our meta-analysis [47][48][49][50][51][52][53][54][55][56][57][58][59]. Exclusion reasons are detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, a sensitivity analysis revealed that its inclusion would not change the results significantly, with an overall prevalence estimate of 34% (95% CI 26-43%). In addition, another paper was discarded due to a lack of access to the full text [91]. Another limitation is that most of the included studies are based on non-probability samples and cross-sectional data from different points in time during the pandemic.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…To the best of our knowledge, to date this is the only research aimed at analyzing the phenomenon of cyberchondria in the general population of internet users during the pandemic. Existing data refer to a narrow group of dental students surveyed by Shailaja et al [ 51 ]. According to this study, as many as 98.7% of 404 answerers were moderately or severely affected by any of cyberchondria symptoms, amid the epidemiological crisis.…”
Section: Discussionmentioning
confidence: 99%